Assembly variation analysis of the aircraft panel in multi-stage assembly process with N-2-1 locating scheme. (October 2019) - Lu, Cong; Huo, Deng-Sheng; Wang, Zi-Yue
The flexible aircraft panel parts are easy to deform during the assembly process, the deformation can directly affect the assembly accuracy of the aircraft panel, and further affect the assembly quality of the aircraft fuselage. In order to evaluate the assembly accuracy of the aircraft panel in multi-stage assembly process with N -2-1 locating scheme, this paper proposes an assembly variation analyzing approach, considering the effect of the contact force between the panel skin and the fixture components on the deformation of the panel in the assembly process. The mathematical models are established to conclude the contact force between the panel skin and the fixture components in multi-stage assembly process of the panel with N -2-1 locating scheme, and the effect of the contact force between the skin and the fixture components on the deformation of the panel in assembly is investigated. An assembly variation model is built for the aircraft panel considering the variation sources including the manufacturing error of the flexible panel parts, fixture error, and the deformation of the panel in multi-stage assembly process considering the effect of the contact force. Finally, the proposed assembly variation analyzing approach for the aircraft panel is tested with a case study.